2020
DOI: 10.1155/2020/1580297
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and Analysis of a Hydraulic Energy-Harvesting Shock Absorber

Abstract: This paper proposes a hydraulic energy-harvesting shock absorber prototype, which realizes energy harvesting of the vibration energy dissipated by the automobile suspension system. The structural design of the proposed shock absorber ensures that the unidirectional flow of oil drives the hydraulic motor to generate electricity while obtaining an asymmetrical extension/compression damping force. A mathematical model of the energy-harvesting shock absorber is established, and the simulation results indicate that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…The results showed that the regenerated energy's root-mean-squared (RMS) was up to 107.94 W at 50 km/h. Wu et al [29] proposed a hydraulic energy-harvesting shock absorber prototype. An energy-harvesting suspension integrated in a hydraulically interconnected suspension system was introduced by Chen et al [30], which can generate up to 421 W at 4 Hz frequency and 40 mm displacement.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the regenerated energy's root-mean-squared (RMS) was up to 107.94 W at 50 km/h. Wu et al [29] proposed a hydraulic energy-harvesting shock absorber prototype. An energy-harvesting suspension integrated in a hydraulically interconnected suspension system was introduced by Chen et al [30], which can generate up to 421 W at 4 Hz frequency and 40 mm displacement.…”
Section: Introductionmentioning
confidence: 99%
“…Further, Li also conducted a research on the dynamic characteristics of regenerative shock absorber with a mechanical check valve, to improve the quality of the regenerated power [22]. Wu and long also proposed a HESA prototype analyze the damping force by varying load resistance [23,24].The main purpose of the research is to optimize the comfort of the vehicle after using the energy-feeding suspension. There is a great energy potential in the car suspension, HESA attract more recognition.…”
Section: Introductionmentioning
confidence: 99%
“…Among all the energy harvesting shock absorbers, the hydraulic energy harvesting shock absorber was put into the application earlier than other types, attributable to its relatively simple structure [ 30 ]. Wu et al [ 31 ] established a mathematical model of the hydraulic energy regenerative shock absorber and conducted a series of bench tests. The results showed that the peak recovery power reached 505.52 W, and the recovery efficiency was 14.5%.…”
Section: Introductionmentioning
confidence: 99%